Acupuncture for early Parkinson’s disease with mild to moderate depression: a randomized controlled trial protocol with functional MRI - Xiao, Hongli; Ren, Yashuo; Yang, Haosen; Wang, Zixi; Li, Zhuohao; Song, Yuguo; Yuan, Xiaojia; Liu, Xiaopeng; Chen, Peng (Frontiers in Neurology, 2024)
ABSTRACT Introduction Depression is a common non-motor symptom of Parkinson's disease (PD), which seriously affects the quality of life of patients with PD. The main clinical treatment method for depression in Parkinson's disease is medication treatment. However, the medication treatment has a long cycle and many adverse reactions. Acupuncture as a non-pharmacological intervention method, has been widely used in the treatment of patients with Parkinson's disease and depressive disorders in China. Therefore, the study of acupuncture in the treatment of early Parkinson's disease with mild to moderate depression has important practical significance. Methods and analysis In this randomized, single-blinded, and placebo-controlled study, a total of 88 patients with Depression in Parkinson’s disease (DPD) will be randomly allocated to either an acupuncture group or a control group in parallel in a 1:1 allocation ratio. Each group will receive 30 min acupuncture treatments or sham acupuncture treatments, 3 times a week, for 12 weeks, followed by a 36-week follow-up period. The primary outcome is the response rate of the Hamilton Depression Scale-17 at 12 weeks. Data will be collected at baseline, at the end of the 12-week treatment period, and during the 12-week and 36-week follow-up. Discussion This study hypothesized that acupuncture may treat DPD by restoring pathological alterations in brain neural activity. The findings will provide scientific evidence for acupuncture in the treatment of early PD with mild to moderate depression. Ethics and dissemination This clinical trial has been approved by the Medical Ethics Committee of the Beijing Hospital of Traditional Chinese Medicine (approval no. 2023BL02-013-01). This trial has been registered with the Chinese Clinical Trials Registry (registration no. ChiCTR2300069310). The results will be published in a peer-reviewed academic journal. Trial registration number： ChiCTR2300069310